THE EFFECT OF JIGSAW TYPE OF COOPERATIVE LEARNING ON CRITICAL THINKING ABILITY OF JUNIOR HIGH SCHOOL STUDENTS - Tamur, Maximus; Subaryo, Subaryo; Ramda, Apolonia H; Nurjaman, Adi; Fedi, Sebastianus; Hamu, Aleksander (Journal of Honai Math, 2021)
Critical thinking ability is an essential component of the four skills needed in the 21st century. However, this ability is still challenging to achieve well by students because of the lack of communication and cooperation during learning mathematics. Therefore, this experimental study with a posttest-only control design was conducted to determine the effect of using the jigsaw cooperative learning model on students' mathematical critical thinking skills. This study involved 62 students consisting of 31 students for the experimental class and 31 students for the control class. Data were analyzed using parametric statistics, namely t-test. The calculation of effect sizes is carried out to determine how much influence the Jigsaw cooperative model has on critical thinking skills using the Hedges'g equation. The analysis results concluded that the critical thinking skills of students who were taught using the jigsaw cooperative learning model were better than those taught using the direct learning model, at a significance level of 0.05. Further analysis obtained an effect size of 0.64, indicating that jigsaw cooperative learning has a moderate effect on students' critical thinking skills. These results provide helpful information for educators and researchers to consider mediators that might mediate the implementation of the learning method in the future.